(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
Heat induced denaturation of bovine serum albumin (BSA) in dimethylsulfoxide (DMSO) containing solutions in the presence of potassium iodide has been studied using UV/vis spectroscopy method. It has been shown that the thermal stability of protein depends on competitive interactions taking place in the solution. At low DMSO concentrations (5 vol. %) BSA is more stable than at higher concentrations (10–25 vol. %).